Comparative Analysis of Psychological and Pedagogical Consulting - Biloshytska, Tetyana (Pedagogical Discourse, 2013)
The notion of psychological consulting is revealed. Pedagogical consulting as a kind of scientific methodical accompaniment of professional activity of a pedagogue is investigated and the author gives her own definition of this notion. Comparative analysis of psychological and pedagogical consulting is made. Their interrelation is studied. The author defines the common features of psychological and pedagogical consulting and their main differences according to different criteria.